2020
DOI: 10.3390/ijms21186454
|View full text |Cite
|
Sign up to set email alerts
|

Neuroinflammatory Mechanisms in Ischemic Stroke: Focus on Cardioembolic Stroke, Background, and Therapeutic Approaches

Abstract: One of the most important causes of neurological morbidity and mortality in the world is ischemic stroke. It can be a result of multiple events such as embolism with a cardiac origin, occlusion of small vessels in the brain, and atherosclerosis affecting the cerebral circulation. Increasing evidence shows the intricate function played by the immune system in the pathophysiological variations that take place after cerebral ischemic injury. Following the ischemic cerebral harm, we can observe consequent neuroinf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
319
1
29

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 409 publications
(353 citation statements)
references
References 192 publications
(229 reference statements)
4
319
1
29
Order By: Relevance
“…In particular, TGF-β promotes the shift of CD4 + T lymphocytes towards the T reg phenotype and the transdifferentiation of myofibroblasts into mature fibroblasts after myocardial infarction 80,81 ; similarly, TGF-β3 inhibits the proliferation of neutrophils, astrocytes and microglia while promoting neuron survival after ischaemic stroke. 82 Overall, we can affirm that about all cell populations involved in the inflammatory response to acute ischaemia are involved in both amplification of damage and in its subsequent healing; furthermore, post-ischaemic repair should not be regarded as a purely 'good' process, since extended fibrosis predisposes to organ loss of function and failure. In other words, the inflammatory response to an ischaemic damage is finely regulated to achieve the best functional outcome, and any imbalance in this complex regulation could result in acute or chronic complications.…”
Section: Activated Platelets Directly Interact With T Reg Cellsmentioning
confidence: 78%
“…In particular, TGF-β promotes the shift of CD4 + T lymphocytes towards the T reg phenotype and the transdifferentiation of myofibroblasts into mature fibroblasts after myocardial infarction 80,81 ; similarly, TGF-β3 inhibits the proliferation of neutrophils, astrocytes and microglia while promoting neuron survival after ischaemic stroke. 82 Overall, we can affirm that about all cell populations involved in the inflammatory response to acute ischaemia are involved in both amplification of damage and in its subsequent healing; furthermore, post-ischaemic repair should not be regarded as a purely 'good' process, since extended fibrosis predisposes to organ loss of function and failure. In other words, the inflammatory response to an ischaemic damage is finely regulated to achieve the best functional outcome, and any imbalance in this complex regulation could result in acute or chronic complications.…”
Section: Activated Platelets Directly Interact With T Reg Cellsmentioning
confidence: 78%
“…Corroborating studies have reported significant positive associations between stroke events and stroke-associated comorbidities and increasing risks of suicidality [ 42 , 43 , 44 , 45 , 46 ]. While the mechanisms of such events are likely to be closely related to the induction of neuroinflammatory responses during ischemic strokes [ 47 ], we did not find any evidence of neuroinflammation or systemic inflammation in the patient in this case. Such associations have not been reported in the literature, and would be of important interest for further investigations.…”
Section: Discussionmentioning
confidence: 52%
“…Brain ischemia and its consequences in humans are third most frequent cause of disability in 80% of survivors [ 1 ], the second most common cause of dementia, and second leading cause of death in the world [ 2 , 3 , 4 , 5 , 6 ]. Every year brain ischemia affects 17 million people worldwide, of whom 6 million die, and the other 5 million are permanently disabled [ 5 , 7 , 8 ]. The incidence of ischemic stroke in men is around 63 per 100,000 and in women around 59 per 100,000, which suggests that men are more affected by the disease than women [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Every year brain ischemia affects 17 million people worldwide, of whom 6 million die, and the other 5 million are permanently disabled [ 5 , 7 , 8 ]. The incidence of ischemic stroke in men is around 63 per 100,000 and in women around 59 per 100,000, which suggests that men are more affected by the disease than women [ 8 ]. The risk of ischemic stroke is age-related, with about 75% of all cases occurring in patients over 64 years of age, and about 25% of cases occurring in young people, suggesting that the pathology does not only affect the elderly [ 8 ].…”
Section: Introductionmentioning
confidence: 99%